The development of upland red rice under shade trees - Muhidin; Jusoff, Kamaruzaman; Elkawakib, Syam'un; Yunus, Musa; Kaimuddin; Meisanti; Ray, Sadimantara Gusti; Rianda, Baka La (IDOSI Publications, 2013)
Rice is an important staple food in Asian populations. World's major rice producing countries are Thailand, China and Vietnam, while Indonesia is the main consumer of rice. Future demand for rice is expected to increase, in line with the population growth. Upland red rice is an important staple food and is often used as a complementary food for local food staples such as sago. General constraints in the development of upland red rice among others are low crop productivity, relatively long harvest time and lack of farmers' land. The efforts should be made to develop upland red rice as the intercrop under forest trees in an agro forestry farming system. Therefore, in such conditions there is a dire need to develop upland red rice that is tolerant to low light conditions.